2017
DOI: 10.11604/pamj.supp.2017.27.2.10569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polio eradication activities on routine immunization: lessons from the 2013 outbreak response in Somali region of Ethiopia

Abstract: IntroductionEthiopia experienced several WPV importations with a total of 10 WPV1 cases confirmed during the 2013 outbreak alone before it is closed in 2015. We evaluated supplemental immunization activities (SIAs), including lessons learned for their effect on the routine immunization program during the 2013 polio outbreak in Somali regional state.MethodsWe used descriptive study to review documents and analyse routine health information system reports from the polio outbreak affected Somali regional state.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…RHIS data have been used to evaluate a wide range of interventions, ranging from programs that targeted specific diseases to interventions or policies that affected multiple types of diseases or health services. These included: the effect of malaria control strategies [30][31][32][33][34][35][36], user fee exemption policies [37][38][39][40], health financing schemes [41][42][43][44], interventions on health governance [45][46][47][48][49][50][51][52][53], the administration of new vaccines and vaccination campaigns [54][55][56], as well as community-level interventions such as approaches to enhance community participation and improve referrals from traditional birth attendants in increasing the demand for maternal and child care [57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…RHIS data have been used to evaluate a wide range of interventions, ranging from programs that targeted specific diseases to interventions or policies that affected multiple types of diseases or health services. These included: the effect of malaria control strategies [30][31][32][33][34][35][36], user fee exemption policies [37][38][39][40], health financing schemes [41][42][43][44], interventions on health governance [45][46][47][48][49][50][51][52][53], the administration of new vaccines and vaccination campaigns [54][55][56], as well as community-level interventions such as approaches to enhance community participation and improve referrals from traditional birth attendants in increasing the demand for maternal and child care [57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…RHIS data have been used to evaluate a wide range of interventions, ranging from programs that targeted speci c diseases to interventions or policies that affected multiple types of diseases or health services. These included: the effect of malaria control strategies [30][31][32][33][34][35][36] , user fee exemption policies [37][38][39][40] , health nancing schemes [41][42][43][44] , interventions on health governance [45][46][47][48][49][50][51][52][53] , the administration of new vaccines and vaccination campaigns [54][55][56] , as well as community-level interventions such as approaches to enhance community participation and improve referrals from traditional birth attendants in increasing the demand for maternal and child care [57][58][59] .…”
Section: Resultsmentioning
confidence: 99%
“…There are 21 local government areas (LGAs), 225 administrative wards and 4 traditional Emirates in Kebbi State. The study focused on 10 LGAs of Kebbi State, namely Bagudo, Danko-Wasagu, Fakai, Gwandu, Koko-Besse, Ngaski, Sakaba, Shanga, Yauri, and Zuru.…”
Section: Study Areamentioning
confidence: 99%
“…Some studies showed SIAs' supportive (strengthening) effect on RI while others showed contrary findings (ie, weakening effect on RI). [7][8][9][10][11] In light of the above, this study would provide a better understanding of the relationships between SIAs and RI, and provide immunization program managers and decision makers more robust evidence that will inform planning, resource mobilization, project implementation, and supportive supervision. Consequently, we assessed the contribution of SIAs on access and utilization of RI services in Kebbi State, northwestern Nigeria.…”
Section: Introductionmentioning
confidence: 99%